Captain John H. Rogers, Texas Ranger - Spellman, Paul N. (Frances B. Vick series ;, 2003)
John Harris Rogers served in Texas law enforcement for more than four decades. He is recognised in history as one of the legendary "Four Captains" of the Ranger force. Paul N. Spellman presents a full-length biography of this enigmatic man